Topographic study of H. pylori and gastric intestinal metaplasia in patients with dyspepsia in a tertiary health care setting. - Dr. R. Jawahar; Dr. Renu G’Boy Varghese; Dr. Thomas Alexander; Dr. George Kurian (Tropical Journal of Pathology and Microbiology, 2019)
Background & Objectives: Dyspepsia is a relatively common clinical condition characterized by chronic / recurrent upper abdominal pain or discomfort and is often associated with one or more of following symptoms at any given time - upper abdominal pain, burning sensation in the chest or upper abdomen, regurgitation, anorexia and early satiety. The present study was done to estimate the prevalence of Intestinal Metaplasia (IM) in the stomach in unselected patients with dyspepsia and to correlate these changes with symptoms, risk factors and endoscopic findings. Methods: We evaluated 102 patients who presented with symptoms of dyspepsia. Relevant clinical details were noted. A minimum of 9 endoscopic mucosal biopsies were taken from all subjects and in addition, biopsies were also taken from endoscopically abnormal areas. Rapid Urease Test (Standard in-house method) was done. All gastric biopsies were graded according to the Updated Sydney System. Statistical analysis was done using Chi-square test. Results: Intestinal metaplasia (IM) was seen in 16.7% of the patients, predominantly in the antrum (10.8%) and all of them showed Type II IM. Atrophic gastritis was again seen predominantly (65.2%) in the gastric antrum and these patients had significantly less (P=0.0065) H. pylori infection. Reflux symptoms were significantly less in patients with IM. Conclusion: We found a prevalence rate of 16.7% of Type II Intestinal Metaplasia of the stomach, which was topographically preponderant in the antrum.